Effects of Rituximab on the Development of Viral and Fungal Infections in Renal Transplant Recipients. (3rd November 2013) - Patel, Samir J.; Devos, Jennifer M.; Knight, Richard J.; Dawson, Kyle L.; Suki, Wadi N.; Gonzalez, Juan M.; Abdellatif, Abdul A.; Gaber, A. Osama
Abstract : Background . Rituximab is becoming increasingly utilized in renal transplant recipients; however, its association with infections remains unclear. Methods . We reviewed the incidence of viral and fungal infections in kidney transplant recipients treated with (n = 55 ) or without (n = 386 ) rituximab (RTX) in addition to standard immunosuppression. Results . Infections occurred in 134 (30%) patients, with a greater proportion in RTX versus no RTX patients (47% versus 28%; P = 0.005 ). Viral infections occurred in 44% and 27% of RTX and no RTX patients, respectively (P = 0.012 ). This was largely driven by the frequency of BK viremia and noncytomegalovirus/non-BK viruses in RTX patients (27% versus 13% (P = 0.011 ) and 15% versus 2% (P < 0.001 ), resp.). Fungal infections also occurred more often in RTX patients (11% versus 3 %; P = 0.009 ). Multivariate analysis revealed deceased donor recipient (odds ratio = 2.5; P < 0.001 ) and rituximab exposure (odds ratio = 2.2; P = 0.016 ) as independent risk factors for infection. Older patients, deceased donor recipients, those on dialysis longer, and those with delayed graft function tended to be at a greater risk for infections following rituximab. Conclusions . Rituximab is associated with an increased incidence of viral and fungal infections in kidney transplantation. Additional preventative measures and/or monitoring infectious complications may be warranted in those receiving rituximab.